Follow-up Analysis of Financial Management Examination Results within the General Election Supervisory Board of Maluku Province - Vendy Ilham Burungasy; Dwi Hariyanti; Ferry H. Basuki (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to determine the extent to which the findings of the BPK and the Inspectorate have been followed up by the Bawaslu of Maluku Province and Bawaslu District. The method used is a qualitative method by taking a number of sample respondents from both Bawaslu, Maluku Province, and Bawaslu District. The results of the interview are then analyzed in the form of narration to draw conclusions. The results showed that the findings of the CPC had been followed up by 20% while the Inspectorate was 53%. The slow follow-up process is caused by several factors, namely: weak leadership commitment, inadequate human resource competence, weak internal control, lack of literacy on legislation and limited infrastructure